Profiling of boiled white corn kernel (binatog) street vendors and determination of food safety knowledge, attitude and practices in Quezon City, NCR, Philippines - Cal Ortiz, Elijah James E. (College of Home Economics, University of the Phillippines Diliman, 2023)
Binatog (boiled white corn kernels), also called bualaw or kinulti is a Philippine snack or dessert often served with a choice of salt or sugar, condensed milk, and shredded coconut. Binatog is often sold by mobile street vendors operating on their bikes roaming different parts of the city for customers. There is a lack of published literature on the production and sale of binatog. As such, this paper aimed to document and profile the binatog industry and investigated binatog street vendors operating in Quezon City, Metro Manila. This paper was able to determine the production and capitalization of binatog as well as identify problems and challenges associated with the industry. Binatog street vendors identified the high cost of raw materials, particularly white corn, as one of the biggest challenges in the industry. The wide prevalence of street foods as well as the susceptibility of binatog to physical, chemical, and microbial contamination warrants investigation on the food safety of the product. The knowledge, attitude, and practices (KAP) of binatog street vendors towards their adherence to food safety was determined and further assessed based on the Philippine Code on Sanitation and other pertinent local laws on food safety. It was found that a majority of binatog vendors in this study possess good to moderate knowledge, generally positive attitudes, and moderate to poor practices towards food safety. Gaps in knowledge on food quality, food contamination, hygiene, and waste disposal were identified which may be a result of their lack of formal food safety training and poor household waste management. Poor knowledge also translated to nonadherence to proper food safety practices, particularly in hygiene, waste disposal, and disease control measures. The researcher suggests that interventions from local health authorities, such as formalization of binatog street vendors, may help in improving the safety of their products as well as allowing better socio economic safety nets. Future studies can consider increasing the scope to determine KAP better statistically and analyze correlation between KAP and sociodemographic factors of binatog vendors. This study may also serve as a baseline assessment of binatog vendors for possible effects intervention measures on KAP.